ASSESSMENT OF THREATS TO PROFESSIONAL ETHICS IN THE PRACTICAL ACTIVITY OF ACCOUNTANTS - CHEBAN, TATIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the study of issues of identification and determination of the level of threats to the professional ethics of professional accountants. Based on the study of the International Code of Ethics for Professional Accountants (including the International Standards of Independence), a description of the threats to compliance with the fundamental principles of ethics of professional accountants, which are divided into five types: threats to self-interest, self-assessment, protection, personal interests and pressure. We have systematized the circumstances that cause these threats, the diversity of which is related to the following situations: preparation and submission of information; offer to provide or receive incentives; the presence of financial interest of a professional accountant in the organization-employer; pressure from managers, management of the employer organization on non-compliance with applicable law and in the event of a conflict of interest. As a result of our research, we proved the nonlinearity of the relationship between circumstances, threats and ethical principles of professional accountants: one circumstance can create several threats, while one threat can affect compliance with several fundamental principles. For example, requiring management to prepare and provide misleading information poses a threat to self-assessment, pressure, and self-interest. At the same time, these circumstances pose a threat of non-compliance with the fundamental principle of objectivity. According to the Conceptual Basis of the Code, a professional accountant must not just follow specific rules, but identify, evaluate and eliminate threats of violation of fundamental principles of ethics. The study of the sequence of actions of the accountant and detailing the factors that should be taken into account, allowed us to visualize the decision-making procedure of the accountant in identifying threats to his ethical behavior and present it as an algorithm. We have proposed a method of differentiated quantitative assessment of acceptable levels of threats, which allows to take into account the probability of their negative impact on compliance with the principles of ethical behavior and the significance of threats for a professional accountant. The use of the provided proposals in practice will promote a more conscious attitude of accountants to the fundamental principles of ethics, will monitor the circumstances that pose a threat to their ethical behavior and will allow more efficient performance of professional tasks.
Keywords: assessment; threat; professional ethics of accountants